Sistema da manejo para a candeia (Eremanthus erythropappus (DC.) MacLeish - Pérez, Jorge Faisal Mosquera (2001)
The objectives of this study were to map native candeia (Eremanthus erythropappus) forest, to adjust equations for estimating the volume of wood, dry matter weight, oil content weight and number of fenceposts, define growth and diameter curves as well as adjust a management plan related to oil content, growth rate and to balanced forest concept. The following data were obteined from a forest inventory and from scaling carried out in a native candeia forest located at the Bela Vista farm, 21°58’23” S e 44°44’35” W, 1,350 to 1700 m of altitude, in Aiuruoca, Minas Gerais, Brazil. The sampling consisted of 18 plots systematically distribuited along the forest, then the diameter and height were measured from individuals having diameter at breast height (dbh) ≥ 5 cm, which were then botanically classifyed. Scaling was done in 63 candeia trees, being distribuited in 6 diameter classes ranging from 5 to 35 cm. The volumes of bole and of branches having a minimum diameter of 3 cm including the bark was calculated through the Huber formula. The number of fenceposts from each scaled tree was also determinated as well as the sampling of leaves and thin branches (diameter > 3 cm). From these sampled material, were determinated the dry matter, weight and oil content weight, being the latter determined through the solvent and vaporizing methods. Ten fragments of candeia trees were mapped, totalling 71.29 ha. The logarithmic Schumacher-Hall model was chosen to estimates the volume, dry matter weight, oil content weight and the number of fenceposts variables. The average stack factor of the bole and branches having diameter up to 3 cm, was of 1.92. The average number of fencepost per tree was 1.10; 2.42; 5.50; 9.20; 8.70 e 13.50 for the respective diameter classes ranging from 5 to 35 cm with a 5 cm class interval for these same the respective average oil contents per tree were found 0.176; 0.465; 1.065; 1.693; 2.805 e 4.481. The number of candeia trees per hectare found for each respective diameter class were 323.69; 111.06; 29.03; 4.32; 5.30 e 2.78. The diameter average growth for candeia tres was of 0.73 cm/year, as identifyed by the stem analysis technique. Of the 16 management plan options for the candeia trees, the best one was that wich presented the DeLiocourt coeficient (q) 2.2 larger than the original q value, 60 % basal area removal and 30 cm maximum diameter. This plan implies on the explotation of 13,3023 m3/ha or 24,476 mst/ha which provided 177,011 kg of oil or 499,1 fenceposts, profting na income of R$ 1.527,35/ha in case the wood would be sold for oil extraction or R$ 1.282,46/ha if they were to be sold as fenceposts.